Skepticism, causality and skepticism about causality - Klima, Gyula; Hall, Alexander W.; Feser, Edward (Proceedings of the Society for Medieval Logic and Metaphysics ;, 2013)
Skepticism, Causality and Skepticism about Causality studies the interrelated themes of causality and skepticism in contemporary, early modern and medieval philosophy. Thomas Aquinas's celebrated proofs of the existence of God (the Five Ways of the Summa Theologica) rely in part on an Aristotelian notion of synchronous causality, wherein the things that exist and persist require an accounting that ultimately terminates in the ongoing activity of a first mover, as the existence and persistence ...